УЛЫЎМА ОРТА БИЛИМ БЕРИЎ МЕКТЕПЛЕРИ ҲӘМ КӘСИП–ӨНЕР КОЛЛЕДЖЛЕРИНДЕ ОҚЫЎШЫЛАРДЫ КӘСИПКЕ БАҒДАРЛАЎДА ҮЗЛИКСИЗЛИКТИ ТӘМИЙИНЛЕЎ МӘСЕЛЕЛЕРИ - Аймухаммедова, Т. (ILIM hám JÁMIYET, 2017)
The article deals with the information about the questions of teenagers’ professional orientation taking into consideration their interests, tendency and abilities. The issues of choosing future professional colleges for further education are shown, and also there are given important directions for cooperation of these institutions to solve this issue.